Pengelolaan Pembelajaran Aktif Inovatif Kreatif Efektif Dan Menyenangkan Dalam Implementasi Manajemen Berbasis Sekolah Di SMP Negeri 1 Karangpandan - TOHARINI, Toharini, Prof. Dr. Yetty Sardjono, M.Si, Drs. Budi Sutrisno, M.Pd (2015)
and Fun in the Implementation of School-Based Management in Secondary School 1 Karangpandan. Graduate Program, University of Muhammadiyah Surakarta. 2014. The thesis of this study to determine and describe the innovative Active Learning Management Creative Effective and Fun (PAIKAM) at SMP Negeri 1 Karangpandan. Subfokus, PAIKEM planning and implementation, evaluation model of learning. Qualitative research methods, ethnographic research design, research conducted in SMP Negeri 1 Karangpandan, data collection by, interviews, observation, document analysis, data analysis through, data reduction, data display, and conclusion. The results of the research that manage schools, which set the whole potential of the school in order to achieve educational goals. PAIKEM, fun learning child-centered means, a child must be active, innovative, creative and effective. Community participation, is a major component implementation process of education, for it needs to be optimized as empowerment in realizing the vision and mission of the school with the new education Dikma. Which is currently in the implementation of Curriculum 2013, the refinement of the SBC with scientific learning needs to be applied. Being in the model is the assessment process eveluasi learning, formative and summative, this is almost the same as curriculum assessment in 2013, because KI KI 1 and 2, the assessment conducted with authentic assessment (process). Besides held improvement and enrichment after summative, assessment results as a document for schools and students.